P488 Switch from intravenous to subcutaneous infliximab in patients with Inflammatory Bowel Disease: efficacy, safety and patients' acceptance. (30th January 2023) - Caballol Oliva, B; Fernàndez-Clotet, A; Panés, J; Masamunt, M C; Gallego, M; Barastegui, R; Vara, A; Giner, À; Ricart, E; Ordás, I
Abstract: Background: A new formulation of biosimilar infliximab (IFX) has recently been approved for subcutaneous administration (SC) that may offer pharmacokinetic advantages resulting in higher drug exposure. Our purpose was to evaluate the efficacy, safety, pharmacokinetic changes and patients' acceptability after switching from intravenous (IV) to SC IFX in a cohort of patients with Inflammatory Bowel Disease (IBD) in clinical practice. Methods: Observational, prospective and single-center study including patients with IBD in sustained (≥6 months) clinical remission under IV IFX that were switched to SC IFX 120 mg every 2 weeks. Prospective monitoring was performed with clinical and laboratory data including IFX trough levels prior to the last IV infusion (W-IV), prior to the first SC administration (W-0), and after 16 weeks (W-16) and 52 weeks (W-52) of SC treatment. Patients' satisfaction has been evaluated at W-52. A descriptive analysis of the data has been carried out with the R Studio statistical program using means and Wilcoxon signed rank test. Results: Sixty patients have been included, all have achieved W-16 and twelve W-52. Thirty-five (58, 3%) are men with a median age of 42, 5 (20-71) years. Thirty-eight (63, 3%) have Crohn's disease and twenty-two (36, 7%) ulcerative colitis, with a median disease duration of 11, 3 years. They have been receiving IV IFX (5mg/kg/8 weeks in 95% of cases) for 5, 7 (0, 6-21, 1) years, at a stable dose (≥6 months). Twenty-seven (45%) received concomitant immunomodulatory treatment and IFX was the first biological in 75% of patients. None of the patients presented clinical relapse during follow-up (Table 1). Median trough IFX levels under IV treatment were 3, 9 µg/dl (W-IV) and 4, 3 µg/dl (W-0). Compared to W-0, IFX trough levels were significantly higher both in W-16 [17, 05 µg/dl (5, 59–57, 60), p<0, 005] and in W-52 [16, 75 µg/dl (8, 65 –35, 01), p=0, 007], without significant differences between W-16 and W-52 (p=0, 74) (Figure 1). None of the patients developed immunogenicity. Three adverse effects have been detected: 1 allergic reaction to the first SC dose and 2 mild skin reactions. At W-16 and W-52 the number of patients maintaining SC IFX treatment were 58/60 (96, 7%) and 10/12 (83, 4%) respectively. At W-52, all patients expressed high satisfaction with the change and would not like to return to IV treatment. All place the SC route as a preference above the IV. Conclusion: Switching from IV to SC IFX is safe, effective, and well accepted by patients with stable IBD. A significant increase in IFX trough levels is observed with the SC formulation.